2019
DOI: 10.1088/1674-1056/28/6/066101
|View full text |Cite
|
Sign up to set email alerts
|

Quantum density functional theory studies of structural, elastic, and opto-electronic properties of ZMoO3 (Z = Ba and Sr) under pressure

Abstract: In continuation of our recent report on molybdates [Appl. Phys. A 124, 44 (2018)], the structural, electronic, elastic, and optical properties of ZMoO3 (Z = Ba and Sr) molybdates are investigated under pressure (10 GPa–50 GPa) comprehensively by deploying the density functional theory. Our investigations show that the studied compounds exhibit stable cubic phase with metallic attributes. The thermodynamic parameters such as enthalpy of formation, Debye, and melting temperatures of the compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…A comprehensive insight into dopant-based nonvolatile RS phenomena has been provided by calculating electronic (band structure and density of states [DOS], isosurface charge density plots, integrated charge density [ICD] plots, and Badar charge analysis), and optical properties. The frequency-dependent (ɷ) complex dielectric function [ε(ω) = ε 1 (ω) + ίε 2 (ω)] has been calculated by following the method described in Reference [39]. The complex dielectric function explored the remaining photosensitive properties like refractive index and optical conductivity using the relations found in Reference [39][40][41].…”
Section: Computational Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive insight into dopant-based nonvolatile RS phenomena has been provided by calculating electronic (band structure and density of states [DOS], isosurface charge density plots, integrated charge density [ICD] plots, and Badar charge analysis), and optical properties. The frequency-dependent (ɷ) complex dielectric function [ε(ω) = ε 1 (ω) + ίε 2 (ω)] has been calculated by following the method described in Reference [39]. The complex dielectric function explored the remaining photosensitive properties like refractive index and optical conductivity using the relations found in Reference [39][40][41].…”
Section: Computational Methodologymentioning
confidence: 99%
“…The frequency-dependent (ɷ) complex dielectric function [ε(ω) = ε 1 (ω) + ίε 2 (ω)] has been calculated by following the method described in Reference [39]. The complex dielectric function explored the remaining photosensitive properties like refractive index and optical conductivity using the relations found in Reference [39][40][41].…”
Section: Computational Methodologymentioning
confidence: 99%
“…The complex dielectric function ε (ω) is known to determine the material response to the electromagnetic field and consists of two parts: ε (ω) = ε 1 (ω) + iε 2 (ω). The imaginary part ε 2 (ω) describes the material's absorption behavior and related to the electronic band structure as follows: [64][65][66][67]…”
Section: Optical Propertiesmentioning
confidence: 99%
“…These compounds have been extensively studied due to novel applications in power generation, fuel cells, spintronics, actuators, magnetic sensors, super-strong composite alloys, supercapacitors, high-pressure optical and magnetic sensors, piezoelectric sensors, and radiation tracers [1][2][3]. Through experiments and theoretical findings, it has been found that most of the aforementioned applications are found in those perovskites that exhibit a multiferroic nature [4][5][6][7] and have a wide band gap of 1.5-3.0 eV, thus serving as good absorbers for solar cells and photochemical applications [8][9][10][11]. Moreover, some of the perovskite compounds have a halfmetallic nature, which allows for their use in useful optical applications in different energy ranges [12,13].…”
Section: Introductionmentioning
confidence: 99%